The formation and properties of helium-degenerate dwarfs - Nelson, L; MacCannell, K; Davis, A (2001)
We have systematically analyzed the evolution of a wide variety of binary systems that ultimately lead to the formation of detached or semi-detached helium degenerate dwarfs (HeDD's). Specifically, we have explored some of the more important dimensions of parameter space including various: (i) metallicities; (ii) mass-transfer rates; and, (iii) states of evolution of the donor at the onset of mass transfer (equivalent to choosing different initial orbital separations). As has been shown in other papers, there is a sharp bifurcation in the evolutionary phenomena that lead to the formation of HeDD's. If the donor star is sufficiently evolved at the onset of mass transfer, then the binary will ultimately evolve to long orbital periods and the HeDD will detach from its Roche Lobe and cool indefinitely. In the other case, the donor continuously loses mass as the binary evolves to very short orbital periods. By examining the evolutionary results for a comprehensive range of starting conditions, the initial properties of HeDD's that undergo cooling can be determined. This is especially important since HeDD's initially cool very quickly and are most likely to be detected when they are relatively luminous. Moreover, many HeDD's are observed as companions in binary millisecond pulsar (BMSP) systems, and thus an accurate evaluation of their initial properties (e.g., surface temperature and luminosity) is central to the estimation of the ages of these systems.